Perlindungan Hak Asasi Manusia dalam Sistem Hukum Pidana - Al Firman; Reyland Silverius Sinaga; Reh Bungana Br PA (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Human Rights are basic rights or basic rights that humans are born with which are naturally inherent in every human being and cannot be contested because they are a gift from God Almighty, or it can be said that human rights are respect for the level and dignity of humans which is a necessary recognition. It is clear that humans are humans. In this research the author uses the Library Research method (library research), studying libraries and other scientific works related to the problem being studied in order to obtain a theoretical and legal basis related to the discussion or problem of the problem being researched. Protection of human rights in criminal law aims to create a justice system that is fair, humane, and in accordance with universal human rights principles. This is an important foundation for preventing limitations on power by criminal institutions and for ensuring that the rights of every individual are respected in the legal process.